Detailed immunophenotyping of B-cell precursors in regenerating bone marrow of acute lymphoblastic leukaemia patients: implications for minimal residual disease detection - Theunissen, Prisca M J; Sedek, Lukasz; De Haas, Valerie; Szczepanski, Tomasz; Van Der Sluijs, Alita; Mejstrikova, Ester; Nováková, Michaela; Kalina, Tomas; Lecrevisse, Quentin; Orfao, Alberto; Lankester, Arjan C; van Dongen, Jacques J M; et al. (British journal of haematology, 2017)
Flow cytometric detection of minimal residual disease (MRD) in children with B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) requires immunophenotypic discrimination between residual leukaemic cells and B-cell precursors (BCPs) which regenerate during therapy intervals. In this study, EuroFlow-based 8-colour flow cytometry and innovative analysis tools were used to first characterize the immunophenotypic maturation of normal BCPs in bone marrow (BM) from healthy children, resulting in a continuous multiparametric pathway including transition stages. This pathway was subsequently used as a reference to characterize the immunophenotypic maturation of regenerating BCPs in BM from children treated for BCP-ALL. We identified pre-B-I cells that expressed low or dim CD34 levels, in contrast to the classical CD34high pre-B-I cell immunophenotype. These CD34-dim pre-B-I cells were relatively abundant in regenerating BM (11-85% within pre-B-I subset), while hardly present in healthy control BM (9-13% within pre-B-I subset; P = 0·0037). Furthermore, we showed that some of the BCP-ALL diagnosis immunophenotypes (23%) overlapped with CD34-dim pre-B-I cells. Our results indicate that newly identified CD34-dim pre-B-I cells can be mistaken for residual BCP-ALL cells, potentially resulting in false-positive MRD outcomes. Therefore, regenerating BM, in which CD34-dim pre-B-I cells are relatively abundant, should be used as reference frame in flow cytometric MRD measurements.
Keywords: buněčná diferenciace; Neoplasm, Residual; Immunoglobulin Heavy Chains; Bone Marrow; Humans; B cells; Antigens, CD34; imunofenotypizace; genová přestavba B-lymfocytů; lidé; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; těžké řetězce imunoglobulinů; antigeny CD34; mladiství; minimal residual disease; předškolní dítě; Immunophenotyping; prekurzorové B-lymfoidní buňky; Male; Flow Cytometry; flow cytometry; Adolescent; Cell Differentiation; kostní dřeň; Regeneration; regenerace; průtoková cytometrie; Precursor Cells, B-Lymphoid; mužské pohlaví; Child, Preschool; pre-B-buněčná leukemie; acute leukaemia; Gene Rearrangement, B-Lymphocyte; reziduální nádor